Should Investors Choose ESG? Empirical Evidence of The Shiller P/E Ratio - Alfredo, Harold Kevin; Anita, Anita; Pratama, Muhammad Irfan (Green Publisher Indonesia, 2024)
This study investigates the CAPE Ratio values of stock issuers in the LQ-45 Index compared to those in the ESG Leaders Index, employing a quantitative approach to assess whether the ESG Leaders Index yields higher returns. The findings reveal that most issuers in both indices are undervalued relative to the LQ-45 Index, indicating potential for future returns. However, the LQ-45 Index has a greater number of overvalued issuers than the ESG Leaders Index. Notably, the study acknowledges limitations, including a lack of exploration into the relationship between the CAPE Ratio and non-financial factors such as ESG scores, and a narrow focus on Indonesian indices without comparative analysis with foreign indices. Future research is recommended to explore these relationships, apply the CAPE Ratio across specific sectors, and compare Indonesia's ESG Index with those in Southeast Asia, thereby enriching understanding of valuation dynamics in relation to ESG factors.